A descrição skinneriana de ensino em livros de psicologia direcionados à formação de professores e critérios para sua produção e publicação - Silva, Leidiany Cristina da (2012)
This work is comprised of two studies. The first one (Study 1) aimed at investigating psychology school books directed to teachers. The objective was analyzing whether the teaching proposals of radical behaviorism were precisely described in the books, and what kind of behavior analysts bibliographical production was used as the basis for the teaching descriptions. Three books were analyzed. Each book was analyzed as regards three aspects: references to Skinner s works, references to the works of other behavior analysts and the descriptive texts about the radical behaviorism approach s on teaching. All kinds of references were analyzed direct and/or indirect quotes and/or final bibliographies. It was observed that the three books had at least one reference to works by behavior analysts. When it was observed the largest number of references to behavior analysts works, there was also a sounder and more up to date theoretical-conceptual description about the radical behaviorism approach. Two books used a small number of references, when compared to the number of references used in the description of other approaches, which indicates little familiarity with the works of behavior analysts. The analysis of the radical behaviorism s approach on teaching has considered five dimensions about skinnerian approach on the subject (what is to teach?, the teacher s role, how to teach, what to teach), and also critics on the skinnerian approach. It was found that being an expert on the approach could be related to producing more complete descriptions as well as exploring the inter-relationships between the different subject matters worked upon. The Study 2 was proposed in order to identify criteria for publishing books as well as understanding the reasons behind the imprecisions. In order to identify the criteria, this Study was based upon the literature, in the criteria for the evaluation of graduate programs, in interviews with professionals involved in books editoring, and with the authors of the books analyzed on Study 1. It was possible to systematize eight criteria for school books' evaluation: the work as the product of graduate programs; the book as a product of inter-institutionality; the peer evaluation; the author s compromise with the discussion and reformulation asked by the evaluator; the potential impact; the novelty in the field; conceptual precision; applicability of the skinnerian concepts in the learning situation. In order to apply the criteria, two of the books cited on Study 1 were selected, and their authors were interviewed. The book 1 has complied five of the criteria, and the book 2 has complied two of them. The main criterion that was identified was the theoretical-conceptual precision. Given the imprecisions cited in the Study 1, it can be concluded that some of these books and their responsibles have not considered the most fundamental aspect to publishing a book. It is discussed some actions that could revert this negligence with the description of the approach